2012
DOI: 10.1098/rsob.120080
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 is activated by mitochondrial membrane potential depolarization and stimulates Parkin E3 ligase activity by phosphorylating Serine 65

Abstract: SummaryMissense mutations in PTEN-induced kinase 1 (PINK1) cause autosomalrecessive inherited Parkinson's disease (PD). We have exploited our recent discovery that recombinant insect PINK1 is catalytically active to test whether PINK1 directly phosphorylates 15 proteins encoded by PD-associated genes as well as proteins reported to bind PINK1. We have discovered that insect PINK1 efficiently phosphorylates only one of these proteins, namely the E3 ligase Parkin. We have mapped the phosphorylation site to a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
746
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 806 publications
(785 citation statements)
references
References 42 publications
32
746
3
4
Order By: Relevance
“…Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014). Current NMR dynamics analysis of R0RBR parkin:pUb as a proxy for this state shows the IBR domain is considerably less mobile due to engagement with pUb although a large stretch of the tether region remains mobile, an observation not obvious from current crystal structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014). Current NMR dynamics analysis of R0RBR parkin:pUb as a proxy for this state shows the IBR domain is considerably less mobile due to engagement with pUb although a large stretch of the tether region remains mobile, an observation not obvious from current crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn helps recruit parkin to the membrane through binding of pUb to the RING1–IBR region of the E3 ligase (Sauvé et al , 2015; Wauer et al , 2015; Kumar et al , 2017) and subsequent phosphorylation of parkin's Ubl (pUbl) domain (Ordureau et al , 2014). These two events greatly stimulate ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014) through an allosteric displacement mechanism of the pUbl domain from parkin (Kumar et al , 2015; Sauvé et al , 2015). What is less clear is how parkin positions the E2~Ub conjugate to enable transfer of the Ub molecule to the RING2(Rcat) domain as a necessary step for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since an insect orthologue of PINK1 from Tribolium castaneum (beetle; TcPINK1) was shown to be catalytically active [4], we substituted TcPINK1 M294 which is equivalent to M318 of human PINK1 with Alanine. Recombinant myelin basic protein (MBP)-tagged wild-type TcPINK1 and the mutant MBP-TcPINK1 M294A were purified and tested for their kinase activity in the presence or absence of 3-MB-PP1 or 1-NA-PP1.…”
mentioning
confidence: 99%
“…The PP1 analog 1-NA-PP1 inhibited Parkin translocation in cells expressing PINK1 AS , but not in cells expressing PINK1 WT , demonstrating the specificity of the inhibition ( Figure 1A and 1B). PINK1 is known to phosphorylate Parkin in response to mitochondrial depolarization, which leads to a mobility shift of Parkin protein band in immunoblotting assays [4][5][6] (Figure 1C). In the presence of 1-NA-PP1, the slower migrating Parkin band is completely absent ( Figure 1C), suggesting that PINK1 kinase activity is required for Parkin modification.…”
mentioning
confidence: 99%
“…It has been shown that PINK1 phosphorylates Parkin on serine 65 of its ubiquitin-like (Ubl) domain, leading to an increase of its ubiquitination activity [6]. However, PINK1 must play an additional role in Parkin activation since the non-phosphorylatable S65A mutant of Parkin is still able to translocate to mitochondria (albeit more slowly), whereas PINK1 deletion or mutation completely abolishes translocation [1].…”
mentioning
confidence: 99%